A Systematic Review and Meta-Analysis on the Management and Outcome of Isolated Skull Fractures in Pediatric Patients - Lucca B. Palavani; Raphael Bertani; Leonardo de Barros Oliveira; Sávio Batista; Gabriel Verly; Filipi Fim Andreão; Marcio Yuri Ferreira; Wellingson Silva Paiva (MDPI AG, 2023)
Background: The impact of traumatic brain injury (TBI) on the pediatric population is profound. The aim of this study is to unveil the state of the evidence concerning acute neurosurgical intervention, hospitalizations after injury, and neuroimaging in isolated skull fractures (ISF). Materials and Methods: This systematic review was conducted in accordance with PRISMA guidelines. PubMed, Cochrane, Web of Science, and Embase were searched for papers until April 2023. Only ISF cases diagnosed via computed tomography were considered. Results: A total of 10,350 skull fractures from 25 studies were included, of which 7228 were ISF. For the need of acute neurosurgical intervention, the meta-analysis showed a risk of 0% (95% CI: 0-0%). For hospitalization after injury the calculated risk was 78% (95% CI: 66-89%). Finally, for the requirement of repeated neuroimaging the analysis revealed a rate of 7% (95% CI: 0-15%). No deaths were reported in any of the 25 studies. Conclusions: Out of 7228 children with ISF, an almost negligible number required immediate neurosurgical interventions, yet a significant 74% were hospitalized for up to 72 h. Notably, the mortality was zero, and repeat neuroimaging was uncommon. This research is crucial in shedding light on the outcomes and implications of pediatric TBIs concerning ISFs.